Evaluasi kinerja penyediaan air baku Embung Sei Gesek dengan pendekatan Balanced Scorecard - Wisdawaty Situmorang; Nadjadji Anwar; Theresia Sri Sidharti (Universitas Airlangga, 2019)
Retention basin is one of the most reliable water resources infrastructures to supply raw water needs in Bintan Regency, one of them is Sei Gesek Retention Basin. Water debit of Sei Gesek Retention Basindecrease every year. In addition, blooming algae on storage surface,and handling of sedimentationthat has never been implemented is feared to affect the performance of raw water supply. Therefore it is necessary to evaluate the raw water supply ofSei Gesek Retention Basin. In this study, performance evaluation is carried out using a balanced scorecard that uses five perspectives (Critical Performance Area) in measuring the organization performance, namely mission, customers, learning and development, internal business processes, and finance. Grading for the questionnaire refers to assessment guide prepared by the author with using a rating scale 1 to 5. From the study results obtained the performance value for each perspectives they are mission is 4.34; customer is 4.28; learning and development is 4.16; internal business process is 4.24, and financial is 4.25. Therefore, performance of raw water supply for Sei Gesek Retention Basin is considered good.